Conditioned media from adipocytes promote proliferation, migration, and invasion in melanoma and colorectal cancer cells. Issue 10 (9th March 2019) - Ko, Jeong‐Hyeon; Um, Jae‐Young; Lee, Seok‐Geun; Yang, Woong Mo; Sethi, Gautam; Ahn, Kwang Seok
Abstract: Epidemiological evidence suggests that obesity can significantly increase the risk of various cancers, although the mechanisms underlying this link are completely unknown. Here, we analyzed the effect of adipocytes on melanoma and colon cancer cells proliferation, migration, and invasion. The potential effects of conditioned media (CM) obtained from differentiated mouse 3T3‐L1 cells and human adipose tissue‐derived mesenchymal stem cells (hAMSC) on the proliferation, migration, and invasion of B16BL6 melanoma and colon 26‐L5 cancer cells were investigated. The 3T3‐L1 and hAMSC CM increased cell proliferation, migration, and invasion in both the cell lines. In addition, adipocytes CM increased matrix metalloproteinase 9 (MMP‐9) and MMP‐2 activity in both B16BL6 and colon 26‐L5 cells. These effects were found to be associated with an increased expression of various oncogenic proteins in B16BL6 and colon 26‐L5 cells. Also, adipocyte CM induced Akt and mTOR activation in both tumor cell lines, and the pharmacological inhibition of Akt and mTOR blocked the CM induced Akt as well as mTOR activation and CM‐stimulated melanoma and colon cancer cell proliferation, migration, and invasion. These data suggest that adipocyte promotes melanoma and colon cancer progression through modulating the expression of diverse proteins associated with cancer growth and metastasis as well as modulation of the Akt/mTOR signaling. Abstract : Obesity has been known to be associated with an increased incidence and mortality from many cancers. Conditioned media (CM) from 3T3‐L1 and hAMSC increased cell proliferation, migration, and invasion in both B16BL6 and colon 26‐L5 cells >CM increased MMP‐9 and MMP‐2 activity in both B16BL6 and colon 26‐L5 cells. Adipocyte could promote melanoma and colon cancer progression through modulating the expression of diverse proteins associated with cancer growth, metastasis, and regulating the Akt/mTOR signaling.